How Investment, Wage Rates, and Output Impact Screen Printers Need for Workers in Palangka Raya - Br. Ginting, Maria Febrina Laurencia (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2023)
This study aims to examine the impact of Capital, Wage Level, and Production Amount on Labor Absorption in the Screen Printing Industry in Palangka Raya City. The present study used the technique of multiple linear regression analysis. Multiple linear regression analysis is a statistical technique employed to assess the impact of multiple predictor variables (independent variables) on a given dependent variable. This study employs a quantitative research methodology intending to substantiate a hypothesis. Data was collected using observation, interviews, questionnaires, and documentation. A simple random selection procedure was employed to choose a sample of 38 respondents from the screen printing sector for this study. The findings derived from the data analysis indicate that the variables of wage rate and productivity exhibit a statistically significant and favorable impact on employment within the screen printing industry. In the context of the screen printing sector, it is seen that capital exerts a detrimental and statistically negligible effect on work